Parenteral penicillin for children with meningococcal disease before hospital admission: case-control study - Harnden, Anthony (BMJ Publishing Group Ltd., 2006)
Objective To explore the impact on mortality and morbidity of parenteral penicillin given to children before admission to hospital with suspected meningococcal disease. Design Retrospective comparison of fatal and non-fatal cases. Setting England, Wales, and Northern Ireland; December 1997 to February 1999. Participants 158 children aged 0-16 years (26 died, 132 survived) in whom a general practitioner had made the diagnosis of meningococcal disease before hospital admission. Results Administration of parenteral penicillin by general practitioners was associated with increased odds ratios for death (7.4, 95% confidence interval 1.5 to 37.7) and complications in survivors (5.0, 1.7 to 15.0). Children who received penicillin had more severe disease on admission (median Glasgow meningococcal septicaemia prognostic score (GMSPS) 6.5 v 4.0, P = 0.002). Severity on admission did not differ significantly with time taken to reach hospital. Conclusions Children who were given parenteral penicillin by a general practitioner had more severe disease on reaching hospital than those who were not given penicillin before admission. The association with poor outcome may be because children who are more severely ill are being given penicillin before admission.